Effects of a fruit and nut diet - Bardshar, Marie (My University, 1908)
Introduction: Fruits and nuts have been considered as accessory or supplementary foods, and to be eaten out of hand at odd times, but this idea is rapidly passing away. Because they were not eaten for the nutritive value which they contained, very little scientific study has been given the fruits and nuts compared with the investigations which have been carried on in connection with the more commonly used foods.
Citation: Bardshar, Marie. Effects of a fruit and nut diet. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Diet; Nutrition; Fruits; Nuts; Graduating theses; Senior theses; Theses